PROTECTIVE EFFECT OF BIFIDOBACTERIUM LONGUM SUSPENSION FORMULATED WITH MEDIUM CHAIN TRIGLYCERIDES OIL IN DNBS-INDUCED COLITIS IN SPRAGUE-DAWLEY RATS (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
One of the most common chronic inflammatory diseases that causes extensive damage to the gastrointestinal tract (GIT) is inflammatory bowel disease (IBD). IBD symptoms can range in severity from mild and frequent diarrhea, bloating, and abdominal pain to severe bloody stools, anemia, unconsciousness, and occasionally even death. One of the main contributing factors to the pathophysiology of IBD is gut dysbiosis. The purpose of the current study was to determine how well a probiotic (Bifidobacterium longum) solution in medium-chain triglycerides (MCT) oil protected rats from colitis caused by dinitrobenzene sulfonic acid (DNBS). Sprague Dawley (SD) rats were given DNBS (120 mg/kg/rat) intrarectally to induce colitis, which was then allowed to persist for three days. Rats were randomly assigned to receive either B. longum oil suspension (3 x 106 CFU/g/day orally) or dexamethasone (2 mg/kg/day orally) for 28 days in a row after colitis induction. Body weight, average intake of food and water, histological analysis, colon weight, intestinal inflammatory biomarkers (fecal calprotectin), antioxidant potential (glutathione (GSH) and superoxide dismutase (SOD)), and biomarkers of oxidative stress (nitric oxide (NO) and malondialdehyde (MDA)). The disease activity index (DAI) and colonic mucosal damage index (CMDI) scores were used to assess the extent of colonic damage. The statistical analysis was conducted using GraphPad Prism software, with a significance threshold of p < 0.05. Body weight and food and water intake were significantly reduced in the DNBS-induced colitis group, while it was prevented by dexamethasone and B. longum oil suspension. Similarly, the degree of colonic damage brought on by DNBS was considerably reduced by dexamethasone and B. longum oil suspension therapy. This impact was followed by considerable improvement in the antioxidant biomarker levels (GSH and SOD) and reduction in the oxidative stress and intestinal inflammation level. Dexamethasone treatment outperformed B. longum oil suspension therapy in every analyzed metric. The study's findings demonstrate the protective effects of B. longum oil suspension therapy and dexamethasone in a DNBS-induced experimental colitis model. This effect may be explained by the anti-inflammatory and antioxidant properties of the treatments.